The roots and policies of the Republic of China-on-Taiwan's foreign policy of pragmatic diplomacy, 1988-1996 - Davies, Martyn J. (My University, 1998)
The rationale of this study is 10 examine the Republic of China (ROC)-on-Taiwan':; foreign policy of "pragmatic diplomacy". The thesis is designed to contribute to the understanding of the developm ent and progression of the ROC-on- Taiwan's foreign policy development, from that of authoritarian to democratic state. This is to be viewed in the context of the international environment in which the ROC government has had to operate - one of growing political isolation. The foreign policy of pragmatic diplomacy had both domestic and international origins - domestic in the domain of Taiwan's internal political development and internatiorul in the realm of Taiwan's international political pariah status. The principal objective of this doctoral thesis is to trace pragmatic diplomacy's political roots, examine its policies, and assess its prospects. Pragmatic diplomacy was officially adopted as a foreign policy by the ROC following the appointment of Lee Teng-hui as president in January 1988. However, rather than marking a distinct change in policy, pragmatic diplomacy was a continuance of the foreign policy track which had been started by Chiang Ching-kuo who had assumed the presidential office from his father Chiang Kai-shek in April 1975. The increasing international isolation of the ROC required a radical foreign policv response from Taipei. The ROC's expulsion from the United Nations in 1971 and subsequent incremental diplomatic de-recognition by its poll 'ical allies necessitated policy reform by the KMT government. This was not forthcoming .inder Chiang Kai-shek, Signs of pragmatism in policy-making began to arise under tile Chiang Ching-kuo administration. This trend continued and was formalised under Lee Teng-hui, Pragmatic diplomacy was designated as an official foreign policy under the Lee Tenghui presidency. Providing an historical background to pragmatic diplomacy, this study will pursue Taiwan's foreign policy progression and account for its development since 1949. The primary focus of the study is, however, on the period 1988 to 1996, from the official beginning of pragmatic diplomacy to the end of the process of democratic transition with the ROC-on- Taiwan's first direct presidential election in 1996. This was the "honeymoon" period of Taiwan's move away from an authoritarian system of government. It was during this eight-year period that Taipei's foreign policy underwent a dramatic shift in focus, one which cast off the restrictions placed upon it by domestic authoritarian politics to one which became accountable to the populace under the island's democratic transformation. For the purposes of this study, the fcreign policy of the ROC will be examined from 1949 with the removal of the ROC's seat of government from the mainland to Taipei, Taiwan. This came as a direct result of the defeat of Chiang Kai-shek's Nationalist Kuomintang (KMT) forces to the Chinese Communist Party (CCP) in the Chinese civil war. Following its expulsion from the mainland by the Chinese Communists, the island of Taiwan became the refuge of the ROC government under the control of the KMT. The post World War II legal status of Taiwan had previously been set out in the November 1943 Cairo Declaraticn which stated that "all territories Japan had stolen from the Chinese, such as Maner.aria, Formosa [Taiwan}, and the Pescadores, shall be returned to the Republic of China. " In July 1945, the heads of government of the United States (US), Great Britain, and the ROC further declared in the Potsdam Declaration that "the terms of the Cairo Declaration shall be carried out. "This was later adhered 10 by the Soviet Union, France, and Japan. Shortly thereafter, Chinese troops occupied Taiwan with the territory being declared a province of China. In 1949, the government of the ROC was moved from Nanking to Taipei! while the CCP created a new regime, the People's Republic of China (PRe), in Beijing.' The result was two rival governments both claiming to be the sale legal representative of the Chinese state, each wanting to reunify the country in its own image. Since the claim to legitimacy was mutual, the "one China principle" whereby each claimed to be the rightful and legal representative of the state of China, was paramount in the internal and international politics of each regime. This was of particular importance to the ROC which was the apparent weaker regime having been exiled to Taiwan, losing the vast majority of its territory, population, and resources in the process. Beijing and Taipei held steadfast to the doctrine of a single Chinese state and as such refused to recognise each others' political existence. Thus the Chinese civil war did not end in 1949 with the expulsion of the KMT from the mainland - it merely continued from a distance. After withdrawing to Taiwan, Chiang Kai-shek proclaimed that one day he would, "counterattack and recover the mainland ." 3 This position formed the rhetorical mainstay of the ROC's polic. for the following three decades. Almost five decades later, this ideal has not been realised and the ROC is still rooted on Taiwan. Since this time, the ROC's reunification policy toward the PRC has shifted from one of military confrontation to one which stresses peaceful political reunification under Sun Yat-sen's ideology of the "Three Principles of the People"." The ROC's policy has become far less hostile over time. The tempering of ROC policy has coincided with Taiwan's economic development, industrial modernisation, and programme of political reform and democratisation. All of these factors have contributed to this change and will be emphasised in this study as having impacted upon Taiwan's foreign policy progression. A moot point of contention which requires clarification is the term "foreign policy" in the case of the ROC. Due to both the ROC and PRC's strict adherence to the one China principle, each side has, and still continues to, regard its policy toward the other as being domestic rather than foreign in nature. This creates difficulties in deh.ung Taipei's policy vis-a-vis the mainland. According to Wilkenfeld, foreign policy can be defined as, " ...those official actions which sovereign states initiate for the purpose 0/ altering or creaung a condition outside their territorial-sovereign boundaries ." 5 Accepting this definition, two questions are raised: firstly, what is the sovereign status of Taiwan?; and secondly, if sovereign, how far, both politically and physically, does the ROC's sovereignty extend? These thematic issues are central to the thesis. Suffice to say at this introductory stage, it is argued that the ROC's mainland (i.e. the PRe) policy was indeed a foreign and not a domestic policy. Since 1949, Taiwan has been ruled by a separate and distinct governmental authority controlled by the KMT. During this half-century period, Taiwan has possessed a different political, economic, and social structure to that which has existed on the mainland under CCP control. Therefore, in reality, and despite its own prior claims to the contrary, the ROC has operated as a distinct dejacto independent entity. Taiwan's policy toward the mainland was thus, to all intents and purposes, «foreign policy. This study will consider it as such.
A thesis submitted to the department of international relations, Faculty of Arts, University of Witwatersrand, Johannesburg, South Africa, for the degree of Doctor of Philosophy. February 1998.
Keywords: China--Relations--Taiwan; Taiwan--Foreign relations; Taiwan--Relations--China